Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Yang, Wenhui; Ye, Liqing; Wu, Yuke; Wang, Xi; Ye, Simin; Deng, Yurong; Huang, Ke; Luo, Hong; Zhang, Jinyi; Zheng, Chengbin (Journal of hazardous materials, 2024)
Millions of people worldwide are affected by naturally occurring arsenic in groundwater. The development of a low-cost, highly sensitive, portable assay for rapid field detection of arsenic in water is important to identify areas for safe wells and to help prioritize testing. Herein, a novel paper-based fluorescence assay was developed for the on-site analysis of arsenic, which was constructed by the solid-phase fluorescence filter effect (SPFFE) of AsH3-induced the generation of silver nanoparticles (AgNPs) toward carbon dots. The proposed SPFFE-based assay achieves a low arsenic detection limit of 0.36 μg/L due to the efficient reduction of Ag+ by AsH3 and the high molar extinction coefficient of AgNPs. In conjunction with a smartphone and an integrated sample processing and sensing platform, field-sensitive detection of arsenic could be achieved. The accuracy of the portable assay was validated by successfully analyzing surface and groundwater samples, with no significant difference from the results obtained through mass spectrometry. Compared to other methods for arsenic analysis, this developed system offers excellent sensitivity, portability, and low cost. It holds promising potential for on-site analysis of arsenic in groundwater to identify safe well locations and quickly obtain output from the global map of groundwater arsenic. [Display omitted] •Arsenic field test kits can detect waterborne arsenic at levels below 1 μg/L.•Solid-phase fluorescence filtration improves sensitivity and selectivity.•Arsenic was successfully detected in river and well water samples.•Portable equipment for on-site arsenic analysis is fast, sensitive, and inexpensive.